Endovascular treatment for restenosis of carotid venous bypass graft: a clinical case report - Bramucci, Alberto; Bianchini Massoni, Claudio; Menozzi, Roberto; Ucci, Alessandro; Epifani, Enrico; Freyrie, Antonio (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Restenosis after open carotid surgery (OCS) represents an issue that experts are very often facing nowadays, both after carotid endoarterectomy(CEA) and carotid bypass(CB). Yet, even if from one side carotid artery stenting (CAS) is currently recommended by most guidelines as treatment of choice for carotid restenosis after CEA, on the other side little is known regarding the best treatment of restenosis after CB. This clinical case report is aimed to empathize the endovascular treatment as an effective therapeutic option for restenosis after OCS. Methods: A 75-year-old woman with severe comorbidities was admitted to our Unit for left carotid bypass graft restenosis. One year earlier, the patient had been treated with left carotid bypass grafting in saphenous vein for infectious complications occurred after CEA for symptomatic left carotid stenosis. The patient underwent a carotid Duplex ultrasonography scan (DUS) which showed a hemodynamically significant left carotid venous graft stenosis with peak systolic velocity of 315 cm/sec; in order to assess the grade of the stenosis a computed tomography angiography confirmed the presence of a significant narrowing of left carotid graft. A carotid artery angiography was performed after 20days, reconfirming the presence of a significant left carotid graft stenosis and was successfully treated with 7x40mm self-expanding stent. Results: The patient had an uneventful post-procedural course and was discharged the day after. After six months, the patient underwent a carotid DUS in our outpatient clinic which confirmed the overall graft and stent patency. Conclusion: CAS represents a feasible therapeutic option for carotid restenosis in patients treated after CB. This clinical case demonstrates that CAS can be performed with acceptable risks and good early results